Jenis kelamin anak, pendidikan ibu, dan motivasi dari guru serta hubungannya dengan preferensi makanan anak sekolah pada anak prasekolah di TK Universitas Muhammadiyah Purwokerto - Atikah Proverawati; Endy Paryanto Prawirohartono; Tjahjono Kuntjoro (Jurnal Gizi Klinik Indonesia, 2008)
Background: Preference to foods among children is a predictor of food consumption pattern. Therefore good under- standing on food preference of children, factors related to foods most likes and disliked needs to be studied for  nutrition education and food supply planning for children.Objective: To find out the relationship between children sex, education of mother, and motivation of teachers with preference to foods available in school among preschool children at Muhammadiyah University of Purwokerto.Methods: The study used cross sectional approach by analyzing data of 60 preschool children. Observation and interview were carry out to identify food preference of the children. The independent variables were children sex, education of mothers, and motivation of teachers whereas the dependent variable was preference to foods available in school.Results: Boys liked jellies and quail egg satay whereas girls liked vegetable filled pastry and cracker fries. The result of chi-square test showed that there was difference in food preference between the girls and boys (p<0.05). Education of mothers was also related to preference to foods among children.Conclusion: There were significant relationship between sex and education of mothers with preference to foods available in school among preschool children